A flow cytometry evaluation of anti-FVIII antibodies: Correlation with ELISA and Bethesda assay - Irigoyen, María Belén (2011)
In this study, we describe a flow cytometry (FC) system for detecting antibodies to factor VIII (FVIII) and compare its results with those of enzyme-linked immunosorbent assay (ELISA) that detects both inhibitory (I-Ab) and non-inhibitory (NI-Ab) antibodies and the Nijmegen modification of the Bethesda method, detecting I-Ab. FC was set up in our laboratory. Recombinant FVIII (rFVIII) was coupled to microspheres (FVIII-m) and reacted with different plasma dilutions. Microspheres without rFVIII were used as control (control-m). Captured anti-FVIII antibodies were detected using anti-human IgG. Plasma samples from the following patients with severe haemophilia A (SHA) patients were evaluated: 17 P (patients without I-Ab, <0.5BUmL-1); 13 PI (patients with I-Ab, 1.1-8200BUmL-1). Of these 13, two PI were referred during immune tolerance induction (ITI), and plasmas from 12 healthy donors (HD) were evaluated. Semiquantitative results were given as an index (the highest mean fluorescence intensity ratio between FVIII-m and control-m multiplied by the inverse of the corresponding plasma dilution). Both plasma and serum were suitable for the test. FC agreed with the Bethesda method (r=0.8; P=0.0001). FC and ELISA had 80% of coincidence. Four of 17 patients (23.5%) had NI-Ab by FC, and two of them developed high levels of I-Ab later on. This test provides a useful alternative for measuring FVIII antibodies supplementing Bethesda assay. FC is fast and easy to perform. No more than 200μL of plasma or serum is required especially making it useful for paediatric patients. © 2010 Blackwell Publishing Ltd.